2020
DOI: 10.1128/jcm.02114-19
|View full text |Cite
|
Sign up to set email alerts
|

Reply to Pogue and Heil, “The Clinical Impact of a Negative Molecular β-Lactamase Gene Test for Enterobacteriaceae : Let's Not Let Perfect Be the Enemy of Really Good”

Abstract: Gram-negative bacteria in the United States and agree that these tests can provide tremendous value to antimicrobial stewardship. We further agree with the authors that the use of these tests for de-escalation purposes is optimal when the practitioner has a good understanding of their local resistance patterns. Not all hospitals are equipped with advanced stewardship programs with the expertise and resources to evaluate local epidemiology and interpret molecular resistance genotype tests. The limitation of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Potential reasons for the scarcity of data to support use of RDTs in GN BSI include the increased diversity of pathogenic organisms, the complexity and multifactorial nature of antibiotic resistance, and the potential downstream clinical consequences of missed organism identification and/or phenotypic resistance [ 43 , 44 ]. Overall, in vitro studies have demonstrated high sensitivity and specificity for organisms and resistance determinants; however, these studies typically occur in monomicrobial blood samples with on-panel targets without mention of phenotypic resistance [ 13 , 14 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Potential reasons for the scarcity of data to support use of RDTs in GN BSI include the increased diversity of pathogenic organisms, the complexity and multifactorial nature of antibiotic resistance, and the potential downstream clinical consequences of missed organism identification and/or phenotypic resistance [ 43 , 44 ]. Overall, in vitro studies have demonstrated high sensitivity and specificity for organisms and resistance determinants; however, these studies typically occur in monomicrobial blood samples with on-panel targets without mention of phenotypic resistance [ 13 , 14 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the findings of a study by Spafford and colleagues, genetic resistance markers like CTX-M and KPC are able to identify many Enterobacterales isolates that lack susceptibility to relevant beta-lactams, but a substantial minority of Enterobacterales isolates that are not susceptible to third- or fourth-generation cephalosporins do not have CTX-M ( 10 ). When the presence or absence of a single gene marker (e.g., CTX-M) is used to guide empirical antimicrobial therapy, it is important to consider not only the sensitivity of an assay but also its negative predictive value, which is dependent upon local prevalence of overall resistance and also resistance mechanisms ( 11 ). In the future, characterization and analysis of full genomic data rather than single gene markers could be used to more accurately predict phenotypic susceptibility and resistance ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…The problems are illustrated in an exchange between Spafford et al. ( Spafford et al., 2019 ; Humphries et al., 2020 ) and Pogue and Heil (2020) , regarding the use of genotypic tests for bla CTX-M , bla KPC , and bla NDM in blood culture panels to predict phenotypic resistance or susceptibility to extended-spectrum cephalosporins and carbapenems in gram-negative organisms. The high very major error rates (which indicate false susceptibility to an antimicrobial agent) and variable negative predictive values of the molecular tests by geographic region and hospital type, led Spafford et al.…”
Section: Molecular Tests To Identify Resistance Genes In Positive Blood Culture Bottles and Respiratory Specimensmentioning
confidence: 99%
“…Detection of a CRG has a high positive predictive value as an indicator of phenotypic resistance in most bacterial species; however, the absence of a resistance gene does not always indicate that the organism detected will be phenotypically susceptible to an antibiotic. The problems are illustrated in an exchange between Spafford et al (Spafford et al, 2019;Humphries et al, 2020) and Pogue and Heil (2020), regarding the use of genotypic tests for bla CTX-M , bla KPC , and bla NDM in blood culture panels to predict phenotypic resistance or susceptibility to extended-spectrum cephalosporins and carbapenems in gram-negative organisms. The high very major error rates (which indicate false susceptibility to an antimicrobial agent) and variable negative predictive values of the molecular tests by geographic region and hospital type, led Spafford et al to raise flags of caution regarding the interpretation of genotypic results.…”
Section: Molecular Tests To Identify Resistance Genes In Positive Blood Culture Bottles and Respiratory Specimensmentioning
confidence: 99%